Strategi Pembinaan Spirituallitas Mualaf di Lembaga Mualaf Center Malang - Elsa, Syifa Oktania (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abstract: Spirituality development strategy is a unified plan that is structured systematically in order to achieve a goal. The strategy of spiritual development is an effort to direct someone to understand and live the teachings and values of Islam so that in everyday life there is a relationship between one's relationship with Allah and one's relationship with others. This research was carried out with the aim of: (1) Analyzing the strategy of spirituality development for converts to Islam at the Institute of Converts to the Center of Malang. (2) Knowing the inhibiting/supporting factors for the implementation of spirituality development strategies for converts to Islam at the Center for Religious Affair in Malang. (3) Knowing the implications of spirituality development for converts to Islam at the Malang Center for Converting Institutions. The results of the study show that: (1) The strategy of spirituality development applied by the Institute of Converts to the Center of Malang in its implementation is in line with the concept of the spiritualization component of Muhammad Abduh's tazkiyatun nafs, namely: tazkiyatun aqidah, tazkiyatun ubudiyah, tazkiyatun akhlaq. (2) the overall supporting factor comes from the Malang converts center facility as well as cooperation with several related parties who assist the coaching process, while the inhibiting factor comes from the converts themselves who are still constrained by the problems they face. (3) The implication or impact of spiritual development is that it has a positive influence on converts, being able to help converts in the implementation of worship procedures, and deepening religious knowledge is able to regulate the emotions of converts to be able to live a more calm life.Abstrak: Strategi pembinaan spiritualitas merupakan suatu kesatuan rencana yang terstruktur secara sistematis guna mencapai suatu tujuan. Strategi pembinaan spiritual adalah usaha mengarahkan seseorang agar memahami dan menghayati ajaran serta nilai-nilai agama Islam sehingga mampu diaktualisasikan dalam kehidupan sehari-hari antara hubungan seseorang dengan Allah dan hubungan seseorang terhadap sesama. Penelitian ini dilaksanakan dengan tujuan untuk: (1) Menganalisis strategi pembinaan spiritualitas pada mualaf di Lembaga Mualaf Center Malang. (2) Mengetahui faktor penghambat/pendukung pelaksanaan strategi pembinaan spiritualitas pada mualaf di Lembaga Mualaf Center Malang. (3) Mengetahui implikasi pembinaan spiritualitas pada mualaf di Lembaga Mualaf Center Malang. Hasil penelitian menunjukkan bahwa: (1) Strategi pembinaan spiritualitas yang diterapkan oleh Lembaga Mualaf Center Malang dalam pelaksanaannya selaras dengan konsep komponen spiritualisasi tazkiyatun nafs Muhammad Abduh, yaitu: tazkiyatul aqidah, tazkiyatul ubudiyah, tazkiyatul akhlaq. Dalam pelaksanaanya meliputi, prosesi syahadat (pra-pasca mualaf), pendekatan individu maupun kelompok melalui kegiataan kegamaan, pendekatan konseling. (2) faktor pendukung secara keseluruhan berasal dari fasilitas Mualaf Center Malang serta kerjasama dengan beberapa pihak terkait yang membantu proses pembinaan, sedangkan untuk faktor penghambat berasal dari para mualaf sendiri yang masih terkendala dengan problematika yang dihadapinya. (3) Implikasi atau dampak adanya pembinaan spiritual yakni memberikan pengaruh yang positif kepada mualaf, mampu membantu mualaf dalam pelaksanaan tata cara ibadah, serta pendalaman ilmu agama mampu mengatur emosional para mualaf dapat menjalani kehidupan dengan lebih tenang.